An Analysis of Human Rights Awareness among the Working Professionals in Delhi Region - Misra, Aditya Narayan; Ojha, Tej Narayan; Singh, Abhishek K. (Future Science / FSH-PH Publications, 2023)
Human rights are the rights of every person in any civilized society. Social development is mainly based on social freedom and to enjoy humanity. We are living in a very diverse society where people have different values, religions, colors, and beliefs, but one thing is common, and that is human value. In this paper, the researchers try to understand the level of respect for human rights among the people of a metropolitan city like Delhi. The research mainly focused on working professionals in the Delhi region. The analysis was based on certain criteria to understand the level of understanding of human rights. The study also pointed out that human rights education is very important for social development and must be seriously included in the academic curriculum. The methodology applied in this study for data collection is primary.